Mate choice in naturally inbred spiders: testing the role of relatedness. (November 2019) - Tuni, Cristina; Mestre, Laia; Berger-Tal, Reut; Lubin, Yael; Bilde, Trine
Abstract : Mate preference based on relatedness may evolve in response to costs and benefits of inbreeding avoidance. Whereas mating with closely related individuals can have negative fitness consequences due to inbreeding depression, it may simultaneously be favoured by inclusive fitness benefits. Variation in the fitness payoff shaped by benefits of inbreeding may even lead to preference for mating with kin. We investigated this hypothesis in the social spider Stegodyphus dumicola, a cooperative species in which reproduction occurs among siblings within the group, premating dispersal is lacking and infrequent encounters with unrelated individuals result in homozygous genetic lineages. We tested whether female mate choice is influenced by male relatedness by pairing females with males that differ in the degree of genetic relatedness, namely nest members, non-nest members from the same population and non-nest members from allopatric populations. We recorded premating (male rejections, latency to mating) and mating (copulation duration and interruptions) behaviours. Females showed no preference for partners on the basis of their relatedness during the premating phase, as frequencies of rejections and successful matings did not differ markedly in encounters with nest and non-nest members. This suggests that selection on discriminatory mechanisms may be weakened or lost in species with inbreeding tolerance and in which relatedness between interacting individuals is very high and variance in relatedness extremely low. Unrelated males from the geographically distant population experienced longer copulations than males from the same population. We interpret this finding as depicting a possible scenario of a between-population reproductive barrier or functional incompatibility, which may be the mechanism causing lower fitness in between-population crosses previously documented in these populations. Highlights: Benefits of inbreeding may lead to mate preference for kin. Social spiders inbreed due to lack of dispersal and within nest matings. Our study shows that females do not prefer partners based on their relatedness. Selection on kin recognition mechanisms may be relaxed in this system.